Tari Cucuk Lampah sebagai Perwujudan Do’a Prosesi Pernikahan Masyarakat Muslim Kecamatan Badas Tahun 1990-2000 - Nio Eko Puspita Sari; Ahmad Hanafi (Amorti: Jurnal Studi Islam Interdisipliner, 2023)
Indonesia has so many cultures, cultures in literature, fine arts, theatre, music, and dance, especially traditional dance. However, awareness of the importance of preserving a traditional art is still a matter of concern. This can be proven in a sacred ceremony, while dances that should be included in the agenda can be omitted. An example is the Cucuk Lampah Dance which is performed in a traditional Javanese wedding, which took place in the Badas District, namely the dance began to disappear since 2000. This study aims to analyze the portrait of the Cucuk Lampah Dance in the Badas District in 1990-2000. Cucuk Lampah dance is one of the traditional dance arts in Indonesia. The role of Cucuk lampah is as director of the carnival at traditional Javanese wedding ceremonies. Besides that, cucuk lampah also acts as a conveyer of meaning regarding Javanese cultural values ​​that are adhiluhung in the process or tradition of marriage. The task of Cucuk Lampah in the bridal procession is as the leader of the group. The entourage in question consisted of the two brides, then the good pager, and the daughter of the dhomas. Cucuk Lampah led the group from the changing place to the kuade. This study uses historical research methods which include five steps, namely: topic selection, heuristics, criticism, interpretation, and historiography. The findings in this study are the beginning of the emergence of the Cucuk Lampah Dance in Badas District, namely in 1980. In the late 1990s, Cucuk Lampah began to experience decadence. Whereas in 2000, the Cucuk lampah show in the Badas sub-district was no longer present in Javanese traditional weddings.